Teachers' Reasons for Adopting the Bilingual Approach to English Language Teaching - Yusti Sagita (Faculty of Education and Teacher Training of UIN Palopo, 2024)
The use of L1 in foreign language classes still has pros and cons in some circles of education. Although there are still pros and cons, the use of L1 in education, especially in teaching foreign languages, is now increasingly recognized and considered by many people, so it continues to be used. This study aims to find out the reasons for English teachers using L1. A qualitative approach with a case study research design was adopted to explore teachers' reasons and opinions. The findings of this study are based on interview data (semi-structured interview) and observations collected in two junior high schools located in the Special Region of Yogyakarta. This study examined three junior high school English teachers. The results revealed that the teachers had clear reasons for using L1 (Bilingual Approach). The reasons used by the teachers are as follows; (a) to explain the material, (b) for class management, and, (c) because the students' level of English is still limited.